2D layered MoS2 loaded on Bi12O17Cl2 nanosheets: An effective visible-light photocatalyst. Issue 6 (15th April 2020) - Ma, Jinying; Shi, Lei; Wang, Zhimeng; Ren, Tieqiang; Geng, Zhongxing; Qi, Wei
Abstract: A novel 2D layered MoS2 /Bi12 O17 Cl2 photocatalyst was produced through a simple ultrasonic assisted strategy. Resultant photocatalysts were characterized via XRD, XPS, BET, TEM, EDX mapping, DRS and PL measurements. The results demonstrated that MoS2 layers uniform loaded on Bi12 O17 Cl2 nanosheets surface, which conduced to photoinduced charge migration and enhanced light harvesting capacity. When MoS2 /Bi12 O17 Cl2 photocatalysts were applied for degrading Rhodamine B, the best MoS2 /Bi12 O17 Cl2 photocatalyst presented a higher degraded rate (0.164 min −1 ) than pristine Bi12 O17 Cl2 (0.068 min −1 ). TOC results indicated that degraded rate of Rhodamine B was 92% in 30 min. Finally, a p-n junction mechanism over layered MoS2 /Bi12 O17 Cl2 photocatalyst was presented. This work provides an inexpensive and facile modified method for promoting the photocatalytic property of catalyst, which has a guide role for the synthesis of other efficient photocatalysts.